CO-PYROLYSIS OF HIGH-DENSITY POLYETHYLENE AND WOOD MIXTURES - Ersen, Tuba; Pehlivan, Dursun (Gazi Univ, Fac Engineering Architecture, 2011)
Reclaiming or disposing waste plastics, which have been widely coming about in today's world, by the means other than recycling is among important issues. In this study, co-pyrolysis of high-density polyethylene (HDPE), chosen among municipal plastic wastes, and pine wood powder, chosen as biomass, were investigated. The effects of different pyrolysis parameters (heating rate, final temperature, mixing ratio and sweeping rate) on the yields of products formed from the pyrolysis of mixtures in a fixed bed reactor of were investigated. In the co-pyrolysis of pellets containing HDPE and pine wood in equal proportions, maximum solid yield was obtained at 1 degrees C/min heating rate and for 500 degrees C final temperature under 10 mL/min nitrogen sweeping flow. It was determined that the highest liquid product yield obtained at 5 degrees C/min heating rate and for 700 degrees C final temperature without sweeping.
Keywords: Polyethylene; wood; co-pyrolysis